Animal fibers as water reservoirs for internal curing of mortars and their limits caused by fiber clustering. (18th January 2021) - Antico, F.C.; Rojas, P.; Briones, F.; Araya-Letelier, G.
Graphical abstract: Highlights: Microhardness of the paste increases near the fibers. The size of unhydrated cement particles reduces as fiber dosage increases. Fibers cannot supply all the necessary internal curing water based on chemical shrinkage. 2 kg of fibers per m 3 of mortar is the optimal dosage. Abstract: We present a bottom-up experimental research to address evidence of internal curing of mortars using randomly distributed pig-hair as water reservoirs. Plain and reinforced mortars with pig hair ranging from 0 to 8 kg of fibers per cubic meter of mortar were prepared. The microstructures of plain and reinforced mortars were scanned using electron microscopy and the microhardnesses were measured within the bulk cement paste and cement paste near pig fibers. Electrical resistivity, surface absorption, and residual compressive strength of mortars after freeze-thaw cycles were used to test the effects of internal curing caused by pig hair. Natural fibers used to reinforce mortars increase their toughness and provide part of the necessary water for internal curing, yet internal curing originated by the addition of natural fibers is not proportional to fiber dosage; where the potential to form fiber clusters increases as fiber dosage increases. Results show that there is an optimum fiber dosage that maximizes internal curing caused by these fibers. This study contributes to the research on reinforced mortars with natural fibers to provide sustainable solutions for construction materials.